Stepping on the cracks - Hahn, Mary Downing (Clarion Books, 1991)
In 1944, while her brother is overseas fighting in World War II, eleven-year-old Margaret gets a new view of the school bully Gordy when she finds him hiding his own brother, an army deserter, and decides to help him.